Caregivers’ experiences, challenges, and needs in caring for people with dementia in India: a scoping review - Daniela Lillekroken; Liv Halvorsrud; Heidi Bjørge; Sailaxmi Gandhi; Palanimuthu T. Sivakumar; Alka Rani Goyal (BMC Health Services Research)
Abstract Background As the world’s most populous country, India faces a growing challenge in addressing dementia, in which advancing age remains the strongest risk factor. Approximately 8.8 million Indians over the age of 60 are currently affected by this condition. While much of the research on dementia caregiving focuses on Western societies, caregiving experiences are shaped profoundly by cultural and socioeconomic contexts, which vary significantly in India. Unique social norms, combined with limited resources, make the burden on dementia caregivers in India both distinct and understudied. This scoping review synthesized existing literature on the experiences, challenges, and needs of dementia caregivers in India, providing critical insights for developing culturally tailored support systems and informing public health initiatives. Methods A comprehensive database search for literature was conducted in April 2022 and updated in September 2024 in six databases (Medline, Embase, PsycINFO, CINAHL, Web of Science and Epistemonikos). The databases were systematically searched for original qualitative and quantitative peer-reviewed studies conducted in India between 2000 and 2024. The scoping review was registered with the Open Science Framework and was reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Checklist (PRISMA-ScR). Results After identifying, screening, and reviewing articles for eligibility, we critically appraised and included a sample of 27 studies in this review. The data synthesis process identified three main themes: (1) navigating the dual realities of caregiving: challenges and rewards for family caregivers in India, (2) gaps in support for home-based care: challenges faced by family caregivers in rural parts of India, and (3) addressing the present and future needs of caregivers for people with dementia in India. Conclusion This scoping review reveals the experiences, challenges, and needs of caregivers for people with dementia, including caregiver burden, stress, and poor health among caregivers resulting from inadequate support, insufficient respite care, and a lack of information about dementia. Health and social services offering dementia care are critically needed in India, where population aging is imminent. Trial registration https://doi.org/10.17605/OSF.IO/4MJDC .